Asymmetric C-H and N-H Functionalization of Indoles Involving Central Chirality via Chiral Phosphoric Acid Catalysis - Gashaw, Alemayehu; Debeli, Dereje K.; Chemeda, Meseret (Mini-Reviews in Organic Chemistry, 2022)
The C-H and N-H functionalization of indoles is an interesting area of research that has a useful impact on organic synthesis due to the availability of chiral indole scaffolds in the discovery of drugs, synthetic bioactive compounds, and natural products. The Chiral Phosphoric Acid catalysts (CPAs) have proven to be a powerful and versatile class of enantioselective organocatalysts. Many asymmetric syntheses of organic compounds have been carried out with these catalysts in C-C and CN bond formation reactions, and great progress has been reported. By 2011, several reviews were published covering some important topics and recent achievements in this field. Therefore, in this review, the most recent advances, research breakthroughs with key examples involving mechanisms of CPA-catalyzed C-H and N-H functionalization of indoles to form central chirality via Friedel Crafts, Michael type, and rearrangement reactions were reviewed and reported.
Keywords: chiral phosphoric acid